2022
DOI: 10.1055/s-0042-1744389
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Team Communication with a Clinical Texting System at a Midwestern Academic Hospital

Abstract: Background Hospitals are increasingly replacing pagers with clinical texting systems that allow users to use smartphones to send messages while maintaining compliance for privacy and security. As more institutions adopt such systems, the need to understand the impact of such transitions on team communication becomes ever more significant. Methods We conducted focus groups with hospitalists and individual interviews with nurses at one academic medical center in the Midwest. All interviews and focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Phatic uses signaled that a message had been received or that a plan of action had been acknowledged. This usage is notable, as one study found that some clinicians are frustrated by receiving phatic messages along the lines of “OK thanks,” believing the additional message to be a superfluity and a burden on their time . However, such phatic acknowledgment may also serve the clinically relevant function of confirming a shared understanding of a given medical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phatic uses signaled that a message had been received or that a plan of action had been acknowledged. This usage is notable, as one study found that some clinicians are frustrated by receiving phatic messages along the lines of “OK thanks,” believing the additional message to be a superfluity and a burden on their time . However, such phatic acknowledgment may also serve the clinically relevant function of confirming a shared understanding of a given medical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also echo those of a focus group on user experiences with clinical texting. In that study, Lee and colleagues discovered that while some users complained about the use of emoji in texts from nurses, others defended it as a way of conveying positive affect. For instance, one participant stated, “The emoji allows there to be another layer of personal interaction.” In our study, even ideograms that conveyed negative affect typically did so in a way that could serve to improve or reinforce the sender’s relationship with the addressee, as has been found in others studies .…”
Section: Discussionmentioning
confidence: 99%
“…The benefits were ease of access, ability to send pictures, and ability to have a record of the conversation. The risks were implementation challenges, high volume of texts, and lack of shared understanding about appropriate texting 23 . One of the authors found the secure chat to be an effective and HIPAA‐secure manner of initiating admission to the hospitalist service from the ED.…”
Section: Conceptual Moral and Legal Foundationsmentioning
confidence: 99%
“…4 5 Despite the prevalence of CTS in clinical care today, little is known about how clinicians use these systems to deliver care and what they are texting when they do. 6 The adoption of CTS has led some clinicians to express concern about its appropriate use, [7][8][9] especially in the context of the high volume of alerts and messages received in a work day. A high volume of messages has been associated with physician burnout and dissatisfaction with time spent on clerical tasks.…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, evaluations of user experiences with CTS have found interprofessional tension in some settings, as some clinicians have expressed frustration about perceived misuse of CTS by others, or receiving messages deemed as 'unnecessary'. [7][8][9] Few studies to date, however, have examined the content of the messages being sent. Doing so requires in-depth content analysis of messages.…”
Section: Introductionmentioning
confidence: 99%